Pharmacological activities of some triazinopyrazolothieno pyrimidine derivatives - Bahashwan Saleh A. (Acta Pharmaceutica)
Triazinopyrazolothieno pyrimidine derivatives 1–5 were evaluated for their anti-inflammatory, analgesic and anticancer activities and acute toxicity. Anti-inflammatory activity of the compounds was studied using the carrageenan test. All tested compounds showed analgesic activity, 3-methoxycarbonyl-4,6-dimethyl-8-[(N-methylindolyl)methyl] pyrimido [5′,4′:4,5]thieno [3′,2′-3,4]pyrazolo [5,1-c]triazine (4) showed activity comparable to that of diclofenac. Compounds 1–5 were also screened for anticancer activity on a human lung cancer cell line (A549) and a human prostate cancer cell line (DU145) using the MTT micro-cultured tetrazolium assay method. Compound 4 showed also significant anticancer activity against both cancer cell lines, comparable to that of doxorubicin. The most active compounds were tested for their acute toxicity and median lethal doses were evaluated.